Public Attitude To Online Loans - Alfadri, Ferri; Aini, Nur; Siregar, Lismayanti (Journal of Islamic Financial Technology, 2022)
With the ease of Peer to Peer Financial Technology (Fintech), it is easier for the community to obtain loan funding assistance. However, this convenience is inseparable from the various problems that occur, such as the many types of loans that are fraudulent or unlicensed (illegal), the spread of personal data and various other things. Thus, this research was conducted to determine people's attitudes towards online loans.This type of research is field research with a qualitative approach. The source of the research data is the community of the Sidimpuan Baru Complex, Silandit Village, South Padangsidimpuan District as many as 10 people. Data was collected by observation and interviews with research informants. The results showed that the informants (debtors) knew well. Informants actively use online loan services because of the ease of the requirements provided, guarantees for the privacy of the borrower's personal data, and feel helped by online loan services. Keywords: Community Attitude, Online Loans, Peer to Peer Lending